Metacognitive strategies and development of reading Comprehension in sixth grade students of the Micaela Bastidas Educational Institution N° 6020. Villa María del Triunfo. Lima - Aiquipa Córdova, Aida Filomena (2024)
The problem at the national level of the lack of understanding at the literal, inferential and criterion levels is almost a constant. Therefore, the objective of this research is to identify if there is a relationship between meta-cognitive strategies and the development of reading comprehension in sixth grade students at the Micaela Bastidas educational institution N.6020. The study with a quantitative approach, hypothetical deductive method, cross-sectional and ordinal level, in a sample of 60 students, the information was obtained with a Likert-type questionnaire survey validated by three expert juries and the reliability measured through Cronbach's Alpha coefficient. Descriptive correlational design. With Spearman's Rho statistician, for the hypothesis contrast it is concluded that there is a moderate significant relationship, r= .236 between metacognitive strategies and the development of reading comprehension in the aforementioned sample, by rejecting the null hypothesis by obtaining a value of less significance to the decision making of 0.05 in sixth grade students of the Micaela Bastidas Educational Institution N° 6020. Villa María del Triunfo. Lime.